Development of a Soil Water Movement Model for the Superabsorbent Polymer Application. Issue 2 (15th February 2018) - Liao, Renkuan; Yang, Peiling; Wang, Zhenhua; Wu, Wenyong; Ren, Shumei
Abstract : Core Ideas: Unstable effects on soil were quantified to obtain time‐varying soil hydraulic parameters. Richards' equation was modified to include the time variable t to simulate soil water movement. Root water uptake was considered in the soil‐water movement model as affected by the SAP. A numerical solution was obtained for root water uptake in soil where SAP was applied. Results guide models of soil change from functional exogenous substances used in soil–crop systems. In dry land farming, the use of a superabsorbent polymer (SAP) can improve rain‐water use efficiency for its unique characteristic of repeatedly absorbing rainfall and slowly releasing it to crop; however, this characteristic creates challenges in modeling water movement in soils after SAPs are applied. A series of experiments were conducted in both the laboratory and the field in an attempt to (i) study the unstable effects of SAP on soil hydraulic parameters and crop root growth; and (ii) determine variation in soil hydraulic parameters after an SAP is applied. A specific model was developed to simulate soil water movement for application of SAPs. In this model, as the unsaturated diffusivity was reduced by 1.2 to 76.6% over the time of SAP application, the time variable t was included in the Richards equation to obtain the time‐varying soil hydraulic parameters. The moisture content of soil layers applied with an SAP was increased by 5.5 to 14.1% after each irrigation event; meanwhile, SAPs enhanced the rate of root water uptake (RWU) to effectively use water. Model validation indicated positive effects of time‐varying soil hydraulic parameters on simulating soil water movement in soils where SAP was applied, and the simulated values had good agreement with measured values. Patterns of water movement in soil layers where SAPs were applied were accurately simulated. The findings of this study provide important guidance for modeling soil water movement when any functional substances are added to soil.